Peningkatan Kualitas Pembelajaran Matematika Bagi Guru SMA Melalui Media Google Classroom dan Geogebra - Aris, Naimah; Erawaty, Nur; Massalesse, Jusmawati; Sirajang, Nasrah; Wahda, Wahda; Kasbawati, Kasbawati; Thamrin, Sri Astuti; Sahriman, Sitti; Ramadhan, Muh. Nur Bahri; Jaya, A. Kresna (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
The involvement of teachers in Bone Regency in using information and communication technology (ICT) to prepare teaching materials is very little or even never said, even though computer facilities and infrastructure are available in the computing lab. This activity aims to provide knowledge to Mathematics teachers about online learning Google Classroom and Geogebra. The use of Google Classroom will make learning more effective for teachers and students because learning is no longer limited by space and time, student can explore learning resources easily and utilize information technology properly. Likewise, Geogebra training is expected to overcome the difficulties of teachers in visualizing concept charts in mathematics dynamically. The target audience for community service is mathematics teachers who are members of the Mathematics MGMP in Bone Regency.